Correction: Wang et al. Identification and Verification of a Novel MAGI2-AS3/miRNA-374-5p/FOXO1 Network Associated with HBV-Related HCC. Cells 2022, 11, 3466 - Chao Wang; Kunkai Su; Hanchao Lin; Beini Cen; Shusen Zheng; Xiao Xu (Cells, 2025)
In the original publication [...]